The place of brush cytology in the differential diagnosis of extrahepatic cholestasis - Şükrü DUMLU; A. Kadir DÖKMECİ and Necati ÖRMECİ and A. Reşit BEYLER and Cemil EKİNCİ and; n UZUNALİMOĞLU (Turkish Journal of Gastroenterology, 2019)
-